Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.35663/amp.2020.371.909
|View full text |Cite
|
Sign up to set email alerts
|

Preparación y control de la enfermedad por coronavirus 2019 (COVID-19) en América Latina

Abstract: Durante las últimas décadas, el mundo se ha expuesto a una serie de amenazas por brotes virales emergentes de diferente índole, los cuales, sólo al estudiarlos en detalle, surge la posibilidad de comprender su verdadero impacto, no sólo de forma inmediata, si no también, a largo plazo. Recientemente, el 12 de diciembre de 2019, la Comisión Municipal de Salud de Wuhan, en la República Popular de China, hizo público un reporte de 27 casos humanos quienes cursaron con una neumonía viral, de los cuales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
49

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 17 publications
(30 reference statements)
0
36
1
49
Order By: Relevance
“…For the moment of the arrival of these cases, the last on March 15, 2020, there were 7,988 cases in Spain. That issue has been a common trend in Latin America now, imported cases from Italy and Spain [27,41,42]. This highlights the relevance of the spread of the COVID-19 due to population movements that has affected Bolivia, but also countries in South America, and most in the Latin American and the Caribbean region.…”
Section: Discussionmentioning
confidence: 88%
“…For the moment of the arrival of these cases, the last on March 15, 2020, there were 7,988 cases in Spain. That issue has been a common trend in Latin America now, imported cases from Italy and Spain [27,41,42]. This highlights the relevance of the spread of the COVID-19 due to population movements that has affected Bolivia, but also countries in South America, and most in the Latin American and the Caribbean region.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, it will allow countries, especially in Latin America, to adopt new measures for epidemiological surveillance, testing, and clinical protocols. For Latin American countries, preparedness and response should be consistent with their states' capacities [15,16].…”
mentioning
confidence: 99%
“…We treated the patient with oxygen inhalation, antibiotics, and nutritional support. Blood gas analysis the second day of hospitalization showed that PCO 2 At the third day, the lung sounds were decreased at the bases, with a saturation of peripheral oxygen of 95%. His platelet counts improved (107 × 10 9 cells/μL) ( Table 1).…”
Section: Case Presentationmentioning
confidence: 99%
“…In late February 2020, the pandemic of the Coronavirus Disease 2019 (COVID- 19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), originated 2 months earlier in China, arrived in Latin America [1][2][3]. In this region, all the countries in South America, have been so far affected with imported cases (since March 2020), mainly from Italy and Spain [2]. After the identification of cases in Brazil and Mexico, other countries in the region begun to report confirmed COVID-19 cases, including Colombia [4,5].…”
Section: Introductionmentioning
confidence: 99%